Measuring propeller pitch based on photogrammetry and CAD - Van, Tuong Nguyen; Le Thanh, Truong; Natasa, Naprstkova (Manufacturing Technology Journal, 2021)
There are a number of methods for measuring propeller pitch but it could be a problem for many fishing boat builders who lack of professional equipment. This paper presents a method of propeller pitch measuring based on photogrammetry and CAD (Computer Aided Design). This method con-sists of three stages. At first, a series of photos of the propeller were taken by a smart phone. After that, these 2D images were processed by a photogrammetry software to create the 3D virtual model of the propeller. Finally, in CAD environment, the pitch at different radii of each blade of the 3D vir-tual model were measured. To validate the proposed method, several propellers for fishing boats were measured and the measuring results were compared to those archived by using an EDM (Electrical Discharge Machining) machine and by a highly skilled man with simple tools. The measurement results show that the proposed method could be acceptable for measuring pitches of propellers of fishing boats.
Keywords: CAD; Fishing boat; Measurement; Photogrammetry; Pitch; Propeller